New fluorimetric assay of horseradish peroxidase using sesamol as substrate and its application to EIA - Hidetoshi Arakawa; Shigeo Nakabayashi; Ken-ichi Ohno; Masako Maeda (Elsevier, 2012)
Horseradish peroxidase (HRP) is generally used as a label enzyme in enzyme immunoassay (EIA). The procedure used for HRP detection in EIA is critical for sensitivity and precision. This paper describes a novel fluorimetric assay for horseradish peroxidase (HRP) using sesamol as substrate. The principle of the assay is as follow: sesamol (3,4-methylenedioxy phenol) is reacted enzymatically in the presence of hydrogen peroxide to produce dimeric sesamol. The dimer is fluorescent and can be detected sensitively at ex. 347Â nm, em. 427Â nm.The measurable range of HRP was 1.0Ã10â18 to 1.0Ã10â15Â mol/assay, with a detection limit of 1.0Ã10â18Â mol/assay. The coefficient of variation (CV, n=8) was examined at each point on the standard curve, with a mean CV percentage of 3.8%. This assay system was applied to thyroid stimulating hormone (TSH) EIA using HRP as the label enzyme. Keywords: Sesamol, Fluorescence, Enzyme immunoassay (EIA), Horseradish peroxidase (HRP), Thyroid stimulating hormone (TSH)